Modified polybenzimidazole blended polyvinylpyrrolidone high-temperature proton exchange membrane, preparation method thereof, membrane electrode and fuel cell

By using modified polybenzimidazole blended polyvinylpyrrolidone high-temperature proton exchange membrane in high-temperature proton exchange membrane fuel cells, the blending ratio and preparation process of OPBI and PVP are adjusted, and the problem of difficult to take into account proton conductivity and mechanical strength is achieved, and efficient and stable fuel cell performance is achieved.

CN119798989AActive Publication Date: 2025-04-11SHANGHAI INST OF SPACE POWER SOURCES

Patent Information

Application Number
CN202411771737.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-11
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing high-temperature proton exchange membrane fuel cells have contradictions between proton conductivity and mechanical strength, which is difficult to take into account both, and the preparation process is cumbersome, which hinders the development of commercialization.

Method used

Modified polybenzimidazole blended polyvinylpyrrolidone high-temperature proton exchange membrane is used to adjust the blending ratio of OPBI and PVP to form an appropriate amount of micro-phase separation structure, improve the proton conductivity, and compensate the membrane plasticization problem caused by PA adsorption through the large skeleton structure of OPBI to ensure mechanical strength.

Benefits of technology

While ensuring mechanical strength, it significantly improves the proton conductivity, simplifies the preparation process, making the membrane electrode voltage higher and the fuel cell power density higher, which is suitable for the application needs of high-temperature proton fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798989A_ABST
    Figure CN119798989A_ABST
Patent Text Reader

Abstract

The invention discloses a modified polybenzimidazole blended polyvinylpyrrolidone high-temperature proton exchange membrane, a preparation method of the modified polybenzimidazole blended polyvinylpyrrolidone high-temperature proton exchange membrane, a membrane electrode and a fuel cell. The modified polybenzimidazole blended polyvinylpyrrolidone high-temperature proton exchange membrane comprises modified polybenzimidazole and polyvinylpyrrolidone, the mass ratio of the modified polybenzimidazole to the polyvinylpyrrolidone is (3 to 1): (1 to 2); the structure of the modified polybenzimidazole is # imgabs0 #, wherein the value range of n is 500 to 1000. According to the high-temperature proton exchange membrane provided by the invention, the proton conductivity is remarkably improved on the premise of ensuring the mechanical strength, and the high-temperature proton exchange membrane is expected to be applied to the field of high-temperature proton exchange membrane fuel cells on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fuel cells, and in particular to a modified polybenzimidazole-blended polyvinyl pyrrolidone high-temperature proton exchange membrane, a preparation method thereof, a membrane electrode and a fuel cell. Background Art

[0002] With the intensification of the global energy crisis and the increasing severity of environmental pollution, it has become a top priority to find clean and efficient energy technologies. Fuel cells, as a technology that directly converts chemical energy into electrical energy, have attracted much attention due to their cleanliness and efficiency. Among the many fuel cell technologies, proton exchange membrane fuel cells are considered to be one of the promising electrochemical technologies for achieving sustainable power generation due to their high efficiency in a wide temperature range, compact structural design, stable operating performance, low cost and small size. Compared with low-temperature proton exchange membrane fuel cells, high-temperature proton exchange membrane fuel cells (HT-PEMFCs) can operate at temperatures of 120℃ to 180℃, and have the advantages of high cell efficiency, simple hydrothermal management, and strong tolerance to CO catalysts. The performance of HT-PEMFCs depends largely on its core component, the high-temperature proton exchange membrane.

[0003] At present, proton exchange membranes based on polybenzimidazole (PBI) are the preferred materials for HT-PEMFC applications. However, there is a certain contradiction between the proton conductivity and mechanical properties of traditional PBI membranes. At present, researchers introduce cross-linking groups into PBI polymers for cross-linking modification to form a cross-linked network in the membrane to improve the proton conductivity and mechanical strength of the proton exchange membrane. For example, Yagmur et al. introduced terephthalaldehyde and ethylene glycol diglycidyl ether cross-linking agents to significantly improve the mechanical strength of the cross-linked membrane compared to the original PBI membrane, from 3.9MPa to 9.6Mpa. However, its proton conductivity compared to the PBI membrane decreased from 0.1030S·cm -1 Reduced to 0.0682S·cm -1 Zheng et al. proposed a two-step method to synthesize a cross-linked PBI membrane by introducing -COOH groups through a grafting reaction in solution and then adding a tetraamine reagent for pre-cross-linking. Compared with the original PBI membrane, the mechanical strength of the two-step cross-linked membrane was increased from 3.93MPa to 9.62MPa, and the proton conductivity was increased from 0.091S·cm -1 Increased to 0.183S·cm -1, thereby improving the mechanical strength and the proton conductivity at the same time. However, the preparation process of the two-step cross-linked PBI membrane is relatively complicated, which hinders its commercial development.

[0004] Although some progress has been made in improving the performance of high-temperature proton exchange membranes, there is still room for improvement, especially in the balance between proton conductivity and mechanical strength. At the same time, a simple preparation process is urgently needed to meet the commercial development and application needs of HT-PEMFCs. Summary of the invention

[0005] The purpose of the present invention is to provide a modified polybenzimidazole-blended polyvinyl pyrrolidone high-temperature proton exchange membrane, which has excellent proton conductivity and can compensate for the plasticization effect caused by doping PA, thereby ensuring the mechanical strength of the proton exchange membrane.

[0006] In order to achieve the above object, the present invention provides a modified polybenzimidazole blended polyvinyl pyrrolidone high temperature proton exchange membrane, comprising modified polybenzimidazole and polyvinyl pyrrolidone, wherein the mass ratio of the modified polybenzimidazole to the polyvinyl pyrrolidone is (3-1): (1-2); the structure of the modified polybenzimidazole is:

[0007]

[0008] The value range of n is 500 to 1000.

[0009] Furthermore, the mass ratio of the modified polybenzimidazole to the polyvinyl pyrrolidone is (3-1):1.

[0010] The present invention also provides a method for preparing the above-mentioned modified polybenzimidazole blended polyvinyl pyrrolidone high temperature proton exchange membrane, comprising:

[0011] Step S1, dissolving polyvinyl pyrrolidone in a polar aprotic solvent to obtain a polyvinyl pyrrolidone solution;

[0012] Step S2, dissolving the modified polybenzimidazole in the polyvinyl pyrrolidone solution, and mixing them evenly to obtain a homogeneous blended solution of the modified polybenzimidazole and the polyvinyl pyrrolidone;

[0013] Step S3, forming a membrane of the blended homogeneous solution by a casting method, heating and evaporating to remove the polar aprotic solvent, to form a modified polybenzimidazole-polyvinylpyrrolidone high-temperature proton exchange membrane;

[0014] Step S4, soaking the modified polybenzimidazole-blended polyvinyl pyrrolidone high temperature proton exchange membrane in phosphoric acid to obtain a phosphoric acid-doped modified polybenzimidazole-blended polyvinyl pyrrolidone high temperature proton exchange membrane.

[0015] Furthermore, the polar aprotic solvent comprises any one or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone or dimethyl sulfoxide.

[0016] Furthermore, the step S1 comprises: stirring the polyvinyl pyrrolidone in the polar aprotic solvent at 60° C. to 80° C. for 1 h to 3 h to obtain the polyvinyl pyrrolidone solution.

[0017] Furthermore, the step S2 comprises: stirring the modified polybenzimidazole in the polyvinyl pyrrolidone solution at 60° C. to 80° C. for 1 h to 3 h to obtain a homogeneous solution of the modified polybenzimidazole and polyvinyl pyrrolidone.

[0018] Furthermore, in step S3, the heating evaporation temperature is 60° C. to 80° C. and maintained for 15 h to 25 h.

[0019] Furthermore, in step S4, the concentration of the phosphoric acid is 70wt% to 98wt%, and the soaking temperature is 90°C to 110°C.

[0020] The present invention also provides a membrane electrode, comprising the above-mentioned modified polybenzimidazole-blended polyvinyl pyrrolidone high-temperature proton exchange membrane.

[0021] The present invention also provides a fuel cell, comprising the above membrane electrode.

[0022] Compared with the prior art, the beneficial effects of the present invention at least include:

[0023] (1) The present invention provides a modified polybenzimidazole blended polyvinyl pyrrolidone (OPBI-PVP) high-temperature proton exchange membrane, which uses OPBI and PVP as raw materials, so that the blended membrane can still be successfully formed when there is a large amount of PVP in the blended membrane, and the preparation of a proton exchange membrane with a blending ratio of OPBI to PVP of (3-1): (1-2) is achieved. Furthermore, when the blending ratio of OPBI to PVP is (3-1): 1, the proton conductivity of the membrane is significantly improved while ensuring the mechanical strength of the proton exchange membrane. On the one hand, the -NH site on the imidazole ring in OPBI and the N atom and carbonyl group in the pyrrole ring in PVP can adsorb PA through hydrogen bonding, which enhances the membrane's adsorption capacity for PA and constructs more proton transmission channels. On the other hand, the blending ratio optimizes the microstructure of the membrane, forms an appropriate amount of microphase separation structure, improves the proton conduction velocity, and ensures the structural stability of the membrane. In this structure, PVP constitutes the hydrophilic region and OPBI constitutes the hydrophobic region. The hydrophilic region improves the hydrophilicity, which is conducive to the hopping conduction of protons, thereby improving the proton conductivity, while the hydrophobic region aggregates to form a hydrophobic network structure, which has a structural strengthening effect. In addition, since the large skeleton structure of OPBI has good structural stability, it can compensate for the membrane plasticization problem that may be caused by high-content PA adsorption, ensuring the mechanical strength of the membrane.

[0024] (2) The present invention also provides a method for preparing an OPBI-PVP high temperature proton exchange membrane, wherein PVP is first dissolved, and then the stepwise dissolution step of OPBI dissolution is added so that OPBI and PVP can be fully dissolved when the blending ratio of the two is similar, thereby ensuring the quality of the membrane. In addition, the high temperature ion exchange membrane can be prepared by forming a film of the blended solution of PBI and PVP by a casting method, and the preparation process is simple, which is conducive to the large-scale development of PBI-PVP high temperature proton exchange membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a graph showing the phosphoric acid absorption and anti-swelling performance of the modified polybenzimidazole-blended polyvinyl pyrrolidone high temperature proton exchange membrane prepared in Examples 1 to 4 of the present invention and the modified polybenzimidazole membrane prepared in the comparative example after being immersed in 85 wt % phosphoric acid at 100° C. for 3.5 hours.

[0026] Figure 2 This is a graph showing the proton conductivity performance of the modified polybenzimidazole-blended polyvinyl pyrrolidone high temperature proton exchange membrane with a phosphoric acid doping rate of 400% prepared in Examples 1 to 4 of the present invention and the modified polybenzimidazole membrane with a phosphoric acid doping rate of 400% prepared in the comparative example under non-humidification conditions in the range of 80°C to 180°C.

[0027] Figure 3This is a fuel cell performance diagram of the modified polybenzimidazole-blended polyvinyl pyrrolidone high temperature proton exchange membrane with a phosphoric acid doping rate of 400% prepared in Examples 1 to 4 of the present invention and the modified polybenzimidazole membrane with a phosphoric acid doping rate of 400% prepared in the comparative example under non-humidified hydrogen and oxygen conditions at 160°C.

[0028] Wherein, OPBI represents a comparative example, OPBI:PVP=3:1 represents Example 1, OPBI:PVP=2:1 represents Example 2, OPBI:PVP=1:1 represents Example 3, and OPBI:PVP=1:2 represents Example 4. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The "Nafion membrane" described herein is a proton exchange membrane material composed of a hydrophobic polytetrafluoroethylene main chain and a hydrophilic sulfonic acid side chain. In the "Nafion membrane", the sulfonic acid side chain constitutes a hydrophilic region, and the polytetrafluoroethylene main chain constitutes a hydrophobic region. These two regions of different properties together form the microphase separation structure of the "Nafion membrane".

[0031] As described in the background technology, there is a certain contradiction between the proton conductivity and mechanical strength of the traditional polybenzimidazole (Polybenzimidazole, PBI) membrane, and the existing improvement methods are either unable to meet the requirements of the PBI membrane while taking into account the proton conductivity and mechanical strength, or the preparation process is relatively cumbersome and the process cost is high. For the PBI membrane, its adsorption capacity for phosphoric acid (Phosphoric Acid, PA) can be improved by cross-linking modification, and more proton transmission channels can be constructed to improve the proton conductivity of the membrane. However, too high PA adsorption (doping) levels will cause the membrane to plasticize (membrane plasticization). The plasticization phenomenon refers to excessive PA adsorption around the polymer main chain, increasing the distance between the polymer chains, resulting in a decrease in the interaction force between the main chains, thereby causing the polymer main chain to plasticize and reduce the mechanical strength of the membrane.

[0032] In order to solve the problem that proton conductivity and mechanical strength are difficult to take into account, the present invention adopts modified polybenzimidazole (OPBI) and polyvinylpyrrolidone (Polyvinylpyrrolidone, PVP) as raw materials, and by adjusting the blending ratio of OPBI and PVP, the blended film formed by OPBI and PVP can simulate the microphase separation structure in the Nafion membrane, promote the rapid transmission of protons, thereby improving proton conductivity. Moreover, the addition of PVP increases the sites for adsorption of PA in the membrane, improves the adsorption capacity of PA, and thus constructs more proton transmission channels to improve proton conductivity. At the same time, the large skeleton structure possessed by OPBI can compensate for the problem of membrane plasticization that may be caused by high-content PA adsorption, and ensure that the mechanical strength of the proton exchange membrane meets the working requirements of the fuel cell. The specific embodiments of the present invention are described in detail below.

[0033] The present invention provides a modified polybenzimidazole-blended polyvinyl pyrrolidone high temperature proton exchange membrane (hereinafter referred to as "OPBI-PVP blended membrane"), comprising modified polybenzimidazole (OPBI) and polyvinyl pyrrolidone (PVP), wherein the mass ratio of the OPBI to the PVP is (3-1): (1-2), and the molecular structures of the OPBI and PVP are respectively as follows:

[0034]

[0035] Wherein, the OPBI can be prepared according to the reference (Hsiu-Li Lin et al., Poly (benzimidazole) -epoxide crosslink membranes for high temperature proton exchange membrane fuel cells, International Journal of Hydrogen Energy (2012)), and the value range of n is 500 to 1000; the PVP is commercially available, and in this example, the value range of m is 500 to 1000.

[0036] In the prior art, due to the relatively poor mechanical strength and film-forming properties of PVP, technicians will limit the amount of PVP added when preparing the blended membrane of PVP and the main polymer to ensure that the mass ratio of the main polymer to PVP exceeds 7:1, so that the membrane can be smoothly formed and maintain its required mechanical strength. However, at this mass ratio, the blended membrane still has the problem of unsatisfactory proton conductivity.

[0037] In the present invention, the inventor unexpectedly discovered that by using OPBI having the structure shown above as the raw material of the blended membrane, the added content of PVP can be greatly increased while ensuring that the membrane can be formed, thereby greatly improving the proton conductivity of the membrane. In some embodiments, the present invention achieves the successful preparation of high-temperature proton exchange membranes with a mass ratio of OPBI to PVP of (3-1):1 and 1:2.

[0038] Furthermore, the inventors have found through research that when the mass ratio of OPBI to PVP is (3-1): 1, the OPBI-PVP blended membrane can greatly improve the proton conductivity of the membrane while ensuring the mechanical strength of the membrane. Specifically, after blending PVP in OPBI, in addition to the -NH site on the imidazole ring in OPBI being able to adsorb PA through hydrogen bonding, the N atom and carbonyl group in the pyrrole ring in PVP can also adsorb PA through hydrogen bonding, thereby improving the adsorption capacity of the membrane for PA, and then constructing more proton transmission channels to improve proton conductivity. Moreover, by controlling the amount of PVP added not to be too high, on the one hand, it is helpful to ensure that the OPBI-PVP blended membrane has sufficient mechanical strength. As mentioned above, excessive PA adsorption levels can cause plasticization of the membrane. Therefore, in order to prevent excessive adsorption of PA due to excessive PVP, the present invention controls the blending ratio of OPBI and PVP. The large skeleton structure of OPBI has good structural stability, which can also compensate for the problem of membrane plasticization caused by high-content PA adsorption, that is, it can make up for the problem of decreased membrane mechanical properties caused by the addition of more PVP. On the other hand, the blending ratio of (3-1):1 also helps to optimize the microstructure of the membrane, so that the hydrophilic properties of PVP can be combined with the hydrophobic properties of OPBI to form an appropriate amount of microphase separation structure and improve the proton conduction rate. PVP is a hydrophilic polymer and constitutes a hydrophilic region in the membrane. OPBI is a hydrophobic polymer and constitutes a hydrophobic region in the membrane. The two regions together form a microphase separation structure. In the microphase separation structure, the hydrophilic region improves the hydrophilicity, which is conducive to the hopping conduction of protons, thereby improving the proton conductivity of the membrane, while the hydrophobic region aggregates to form a hydrophobic network structure. Its structural reinforcement effect ensures the mechanical strength of the membrane.

[0039] In addition, in the prior art, when preparing a blended membrane of PBI and PVP (PBI: PVP ≥ 7: 1), PVP and PBI are generally added to a solvent together for dissolution in the preparation method. However, in the present invention, the inventors found that when the contents of PVP and PBI are similar, a high content of PVP may cause the compatibility of the blended system to deteriorate, so that when PBI and PVP are added to a polar aprotic solvent together, PVP cannot be completely dissolved. This is because when a high content of PVP is added, the interaction between PVP molecules may be enhanced to form larger aggregates, which are difficult to be further dispersed by solvent molecules, resulting in a decrease in the uniformity of the solution. In the preparation method of the present invention, it is innovatively proposed for the first time to adopt a step-by-step dissolution method to achieve full dissolution of PVP and PBI in a solvent. Specifically, the preparation method of the OPBI-PVP blended membrane described in the present invention includes:

[0040] Step S1, dissolving PVP in a polar aprotic solvent to obtain a PVP solution.

[0041] The polar aprotic solvent includes, but is not limited to, any one or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone or dimethyl sulfoxide.

[0042] In some embodiments, the PVP is stirred in the polar aprotic solvent at 60° C. to 80° C. for 1 h to 3 h, so that the PVP is fully dissolved and mixed uniformly in the polar aprotic solvent to obtain a PVP solution.

[0043] Step S2, dissolving OPBI in the PVP solution, and mixing the mixture evenly to obtain a homogeneous solution of OPBI and PVP.

[0044] In some embodiments, the OPBI is stirred in the PVP solution at 60° C. to 80° C. for 1 h to 2 h, so that the OPBI is fully dissolved and mixed evenly in the PVP solution to obtain a homogeneous blended solution of the OPBI and PVP.

[0045] In some embodiments, the preparation method further comprises placing the homogeneous solution of OPBI and PVP in a vacuum drying oven and vacuum defoaming at room temperature for 1 to 2 hours to ensure the uniformity of the film material in the subsequent coating and curing process and reduce defects.

[0046] Step S3, forming a film of the OPBI and PVP blended homogeneous solution by a casting method, heating and evaporating to remove the polar aprotic solvent, and forming an OPBI-PVP blended film.

[0047] In some embodiments, the heating evaporation temperature is 60° C. to 80° C. and maintained for 15 h to 25 h to completely remove the polar aprotic solvent and facilitate film formation.

[0048] Step S4, soaking the modified polybenzimidazole-blended polyvinyl pyrrolidone high temperature proton exchange membrane in phosphoric acid to obtain a phosphoric acid-doped OPBI-PVP blend membrane.

[0049] In some embodiments, the concentration of the phosphoric acid is 70 wt % to 98 wt %, the immersion temperature is 90° C. to 100° C., and the immersion is performed until the phosphoric acid doping rate of the OPBI-PVP blended film reaches 400%.

[0050] Unless otherwise specified, the chemicals used in the present invention are all conventional commercially available chemical reagents. These chemicals can be purchased from a number of chemical reagent suppliers and do not require special preparation or synthesis.

[0051] The present invention is further described in detail below in conjunction with specific embodiments.

[0052] Example 1

[0053] This embodiment provides a modified polybenzimidazole blended polyvinyl pyrrolidone high temperature proton exchange membrane (OPBI-PVP blended membrane), and the preparation method of the OPBI-PVP membrane is as follows:

[0054] Step S101, using OPBI and PVP as raw materials and N-methylpyrrolidone solution as solvent, wherein the mass ratio of OPBI to PVP is 3:1. Adding the PVP into the N-methylpyrrolidone solution, stirring at 80° C. for 1 h to dissolve the PVP, and obtaining a PVP solution.

[0055] Step S102, adding the OPBI into the PVP solution, stirring at 80°C for 3 hours, to obtain a blended solution in which the total mass fraction of PVP and OPBI in the solution is 8 wt%.

[0056] Step S103, placing the blended solution in a vacuum drying oven and performing vacuum defoaming at room temperature for 1 hour.

[0057] Step S104, forming a film by a casting method, casting the blended solution obtained in step S103 on a glass plate, heating in an oven at 60° C. for 20 h, and volatilizing and removing N-methylpyrrolidone to obtain an OPBI-PVP blended film, recorded as OPBI:PVP=3:1.

[0058] Step S105 , soaking the OPBI-PVP blended membrane in 85wt% PA at 100° C. for 1 hour and 30 minutes and then taking it out to obtain an OPBI-PVP blended membrane with a phosphoric acid doping rate of 400%, which is used for subsequent proton conductivity and fuel cell performance tests.

[0059] Example 2

[0060] The difference between this embodiment and embodiment 1 is that in step S101, the mass ratio of OPBI to PVP is 2:1, which is recorded as OPBI:PVP=2:1. In step S105, the OPBI-PVP blended membrane is immersed in 85wt% PA at 100°C for 1 hour and 10 minutes to obtain an OPBI-PVP blended membrane with a phosphoric acid doping rate of 400%. In this embodiment, due to the increase in the content of PVP, the adsorption rate increases accordingly, and the immersion time required for the membrane is less than that in embodiment 1.

[0061] Example 3

[0062] The difference between this embodiment and embodiment 1 is that in step S101, the mass ratio of OPBI to PVP is 1:1, which is recorded as OPBI:PVP=1:1. In step S105, the OPVP-PBI blended membrane is immersed in 85wt% PA at 100°C for 7 minutes to obtain an OPBI-PVP blended membrane with a phosphoric acid doping rate of 400%. In this embodiment, due to the increase in the content of PVP, the adsorption rate increases accordingly, and the immersion time required for the membrane is less than that in embodiment 1.

[0063] Example 4

[0064] The difference between this embodiment and embodiment 1 is that in step S101, the mass ratio of PBI to PVP is 1:2, which is recorded as OPBI:PVP=1:2. In step S105, the OPBI-PVP blended membrane is immersed in 85wt% PA at 100°C for 5 minutes to obtain an OPBI-PVP blended membrane with a phosphoric acid doping rate of 400%. In this embodiment, due to the increase in the content of PVP, the adsorption rate increases accordingly, and the immersion time required for the membrane is less than that in embodiment 1.

[0065] Comparative Example

[0066] The difference between this comparative example and Example 1 is that PVP is not added. The preparation process of the high temperature proton exchange membrane of this comparative example is as follows:

[0067] Step S201, using OPBI as a raw material and N-methylpyrrolidone solution as a solvent, adding OPBI into the N-methylpyrrolidone solution, stirring at 80° C. for 3 hours, and obtaining a uniform solution with a total mass fraction of OPBI in the solution of 8 wt %.

[0068] Step S203, placing the homogeneous solution in a vacuum drying oven and performing vacuum defoaming at room temperature for 1 hour.

[0069] Step S204, forming a film by a tape casting method, casting the uniform solution obtained in step S103 on a glass plate, heating in an oven at 60° C. for 20 hours, and volatilizing and removing N-methylpyrrolidone to obtain an OPBI film, which is recorded as OPBI.

[0070] Step S205 , soaking the OPBI membrane in 85 wt % PA at 150° C. for 1 hour and 30 minutes and then taking it out to obtain an OPBI membrane with a phosphoric acid doping rate of 400%, which is used for subsequent proton conductivity and fuel cell performance tests.

[0071] The different high temperature proton exchange membranes obtained in Examples 1 to 4 and the comparative example were subjected to the following off-line and on-line tests.

[0072] With reference to GB / T 20042.3-2022, the obtained high-temperature proton exchange membrane was tested for swelling rate. The specific operating conditions were as follows: under constant temperature and humidity conditions of 23°C ± 2°C and 50% ± 5%, the initial length L0 and initial width W0 of the sample were measured with a caliper, the thickness d0 of the sample was measured with a thickness gauge, and the initial volume V0 = L0 × W0 × d0 was calculated. After the sample was soaked for 24 hours at room temperature and a phosphoric acid concentration of 85%, the length L and width W of the sample were measured with a caliper, the thickness d of the sample was measured with a thickness gauge, and the volume after soaking V = L × W × d was calculated. The swelling rate E v =V0 / V.

[0073] Referring to GB / T 20042.3-2022, the proton conductivity of the obtained high temperature proton exchange membrane was tested. The specific operating conditions were: at a temperature of 80°C to 180°C and a humidity of 0%, a conductivity test device was connected to an electrochemical impedance tester.

[0074] With reference to GB / T 20042.5-2009, the obtained high temperature proton exchange membrane was made into a high temperature proton exchange membrane fuel cell, and a polarization curve test was carried out. The specific operating conditions were: the operating temperature of the single cell was 160°C, the anode was fed with pure hydrogen, the cathode was fed with normal pressure oxygen, and the ratio of cathode feed to anode feed was 1:1.

[0075] The test results are as follows Figures 1 to 3 shown.

[0076] See also Figure 1 , the phosphoric acid adsorption (doping) rate and swelling rate of the proton exchange membranes prepared in Examples 1 to 4 of the present invention and the comparative example after being soaked in phosphoric acid for 3.5 hours were measured; in the figure, the phosphoric acid soaking time of each proton exchange membrane is the same. As an example, Figure 1 OPBI:PVP=3:1 in the figure represents the test results of the phosphoric acid doping rate and swelling rate of the OPBI-PVP blended membrane obtained by steps S101 to S104 in Example 1 after being soaked in phosphoric acid for 3.5 hours. It can be seen from the figure that after phosphoric acid adsorption, the phosphoric acid adsorption rates of the membranes obtained in Examples 1 to 4 of the present invention and the comparative example were measured to be 444.4%, 604.3%, 639.1%, 880.6%, and 322.9%, respectively. The corresponding swelling rates were 300%, 341%, 362.3%, 406.3%, and 224.5%, respectively. The results show that compared with the comparative example (OPBI), the OPBI-PVP blended membranes prepared in Examples 1 to 4 of the present invention have a higher PA adsorption rate and better acid utilization, which proves that the higher content of PVP blending introduces more PA adsorption sites in the membrane, and the carbonyl group of PVP and the nitrogen atom on the pyrrolidone ring are combined with PA through hydrogen bonds, thereby more effectively adsorbing PA and constructing a proton transport channel, which is beneficial to improve the proton conductivity of the membrane. Moreover, since the blending increases the free volume of the membrane, the membrane can accommodate more PA. However, the high PA adsorption level and the free volume increased by the blending also cause the swelling rate of the membrane prepared in Examples 1 to 3 of the present invention to be relatively high, and the swelling rate of Example 4 is the highest. Although a higher swelling rate may lead to a relative decrease in the mechanical strength of the membrane, the mechanical strength of the membrane prepared in Examples 1 to 3 can still maintain sufficient mechanical strength to meet the application requirements of high-temperature proton fuel cells when the PA adsorption level is high. However, due to the excessively high swelling rate, the mechanical strength of the membrane prepared in Example 4 (OPBI: PVP = 1:2) may not meet the application requirements of high-temperature proton fuel cells. The swelling rate of the film prepared in Example 4 is the highest, proving that too much PVP blending will lead to excessive PA adsorption, resulting in excessive swelling of the film. Too high a swelling rate means that the polymer main chain in the film is easily plasticized, which is not conducive to maintaining the mechanical strength of the film. Therefore, the preferred mass ratio of OPBI to PVP in the OPBI-PVP blend film is (3-1):1.

[0077] See also Figure 2 The proton conductivity of the phosphoric acid doped proton exchange membranes prepared in Examples 1 to 4 of the present invention and the comparative example with a phosphoric acid doping rate of 400% was measured. As can be seen from the figure, at 100°C, the proton conductivity of the membranes prepared in Examples 1 to 4 of the present invention and the comparative example was 0.224 S·cm -1 、0.170S·cm -1 , 0.192S·cm -1 , 0.095S·cm -1 , 0.168S·cm -1 At 160°C, the proton conductivity of the membranes prepared in Examples 1 to 4 of the present invention and the comparative example was measured to be 0.228 S·cm-1 , 0.255S·cm -1 , 0.325S·cm -1 、0.177S·cm -1 , 0.188S·cm -1 . The results show that compared with the comparative example, the proton conductivity of Examples 1 to 3 of the present invention is significantly improved. On the one hand, it proves that the mass ratio of OPBI:PVP=(3~1):1 makes the PA adsorption level in the membrane appropriately improved, and builds more channels for proton transport; on the other hand, it proves that this mass ratio forms an appropriate amount of microphase separation structure in the membrane, and the hydrophilic PVP effectively improves the hydrophilicity of the structure in the membrane, which is conducive to the hopping conduction of protons, thereby improving the proton conductivity. The proton conductivity of the membrane of Example 1 decreased significantly at a temperature greater than or equal to 120°C. Therefore, Examples 2 and 3 are preferred embodiments of the present invention. The proton conductivity of Example 4 is the lowest. This is because the excessively high proportion of PVP blending makes the PA adsorption level too high, causing the plasticization of the membrane. It may also be because too many microphase separation structures are formed, which destroys the stability of the polymer main chain, but makes the proton transmission path complicated or discontinuous, hindering the migration of protons, thereby causing a decrease in proton conductivity.

[0078] See also Figure 3 The fuel cell performance graph of the phosphoric acid doped proton exchange membrane (hereinafter referred to as "phosphoric acid doped membrane") with a phosphoric acid doping rate of 400% prepared in Examples 1 to 4 of the present invention and the comparative example was measured. It can be seen from the figure that at 0.1 A / cm 2 When the membrane electrode voltages prepared by the phosphoric acid doped membranes prepared by Examples 1 to 4 of the present invention and the comparative example were measured to be 0.780 V, 0.760 V, 0.754 V, 0.732 V, and 0.743 V, respectively. The power densities of the fuel cells prepared by the phosphoric acid doped membranes prepared by Examples 1 to 4 of the present invention and the comparative example were measured to be 78.0 mW·cm -2 、76.0mW·cm -2 、75.4mW·cm -2 、73.2mW·cm -2 、74.3mW·cm -2 . At 0.5A / cm 2 When the membrane electrode voltages of the membranes prepared by the phosphoric acid doped membranes prepared by the embodiments 1 to 4 of the present invention and the comparative example were measured to be 0.662 V, 0.660 V, 0.655 V, 0.648 V, and 0.626 V, respectively. The power densities of the fuel cells prepared by the phosphoric acid doped membranes prepared by the embodiments 1 to 4 of the present invention and the comparative example were measured to be 331.0 mW·cm -2 、330.0mW·cm -2 、327.5mW·cm-2 、324.0mW·cm -2 、313.0mW·cm -2 At 1.0A / cm 2 When the membrane electrode voltages prepared by the phosphoric acid doped membranes prepared by Examples 1 to 4 of the present invention and the comparative example were measured to be 0.572 V, 0.578 V, 0.581 V, 0.574 V, and 0.526 V, respectively. The power densities of the fuel cells prepared by the phosphoric acid doped membranes prepared by Examples 1 to 4 of the present invention and the comparative example were measured to be 572.0 mW·cm -2 、578.0mW·cm -2 、581.0mW·cm -2 、574.0mW·cm -2 、526.0mW·cm -2 . At 2.0A / cm 2 When the membrane electrode voltages prepared by using the phosphoric acid doped membranes prepared by Examples 1 to 4 of the present invention and the comparative example were measured to be 0.430 V, 0.434 V, 0.419 V, 0.423 V, and 0.398 V, respectively. The power densities of the fuel cells prepared by using the phosphoric acid doped membranes prepared by Examples 1 to 4 of the present invention and the comparative example were measured to be 860.0 mW·cm -2 、868.0mW·cm -2 、838.0mW·cm -2 、846.0mW·cm -2 、796.0mW·cm -2 . Compared with the comparative example, the membrane electrode voltage of the PA-doped OPBI-PVP blended membrane prepared in Examples 1 to 3 of the present invention is higher, which means that the membrane electrode polarization loss is smaller and the power density of the fuel cell is higher, which proves that the fuel cell prepared by the OPBI-PVP blended membrane prepared by the present invention has good working performance. It should be noted that although the proton conductivity of the PA-doped OPBI-PVP blended membrane prepared in Example 4 of the present invention is low, the power density of the fuel cell prepared by Example 4 is still higher than that of the comparative example, which proves that the PA-doped OPBI-PVP blended membrane also has good oxidation resistance and PA retention ability, which makes the power density of the fuel cell prepared in Example 4 still relatively high.

[0079] In summary, the present invention provides a modified polybenzimidazole blended polyvinyl pyrrolidone (OPBI-PVP) high temperature proton exchange membrane and a preparation method thereof. The present invention significantly improves the proton conductivity while ensuring mechanical strength. The high content of PVP added increases the adsorption sites of PA, thereby enhancing the adsorption capacity of the membrane to PA and constructing more proton transmission channels. The precisely controlled blending ratio optimizes the microstructure of the membrane, forms an appropriate amount of microphase separation structure, improves the proton conduction velocity and maintains the structural stability of the membrane. PVP constitutes a hydrophilic region, OPBI constitutes a hydrophobic region, the hydrophilic region forms a continuous three-dimensional network structure, provides a continuous transmission path for protons, improves proton conductivity, and the hydrophobic region plays a structural reinforcement role. At the same time, the large skeleton structure of OPBI compensates for the membrane plasticization problem that may be caused by high-content PA adsorption, prevents excessive PA adsorption caused by excessive PVP from causing membrane plasticization, and ensures the mechanical strength of the membrane. Furthermore, the preparation method of the OPBI-PVP blended membrane of the present invention successfully realizes the preparation of the membrane under the condition of similar OPBI and PVP contents, has a simple preparation process, and is expected to be widely used in the field of high-temperature proton fuel cells.

[0080] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A modified polybenzimidazole blended polyvinyl pyrrolidone high temperature proton exchange membrane, characterized in that: The invention comprises modified polybenzimidazole and polyvinyl pyrrolidone, wherein the mass ratio of the modified polybenzimidazole to the polyvinyl pyrrolidone is (3-1): (1-2); the structure of the modified polybenzimidazole is: The value range of n is 500 to 1000.

2. The modified polybenzimidazole blended polyvinyl pyrrolidone high temperature proton exchange membrane according to claim 1, characterized in that: The mass ratio of the modified polybenzimidazole to the polyvinyl pyrrolidone is (3-1):

1.

3. A method for preparing a modified polybenzimidazole-polyvinyl pyrrolidone high temperature proton exchange membrane according to claim 1 or 2, characterized in that: Include: Step S1, dissolving polyvinyl pyrrolidone in a polar aprotic solvent to obtain a polyvinyl pyrrolidone solution; Step S2, dissolving the modified polybenzimidazole in the polyvinyl pyrrolidone solution, and mixing them evenly to obtain a homogeneous blended solution of the modified polybenzimidazole and the polyvinyl pyrrolidone; Step S3, forming a membrane of the blended homogeneous solution by a casting method, heating and evaporating to remove the polar aprotic solvent, to form a modified polybenzimidazole-polyvinylpyrrolidone high-temperature proton exchange membrane; Step S4, soaking the modified polybenzimidazole-blended polyvinyl pyrrolidone high temperature proton exchange membrane in phosphoric acid to obtain a phosphoric acid-doped modified polybenzimidazole-blended polyvinyl pyrrolidone high temperature proton exchange membrane.

4. The method for preparing a modified polybenzimidazole-blended polyvinyl pyrrolidone high temperature proton exchange membrane according to claim 3, characterized in that: The polar aprotic solvent comprises any one or more of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone or dimethyl sulfoxide.

5. The method for preparing a modified polybenzimidazole-blended polyvinyl pyrrolidone high temperature proton exchange membrane according to claim 3, characterized in that: The step S1 comprises: stirring the polyvinyl pyrrolidone in the polar aprotic solvent at 60° C. to 80° C. for 1 h to 3 h to obtain the polyvinyl pyrrolidone solution.

6. The method for preparing a modified polybenzimidazole-polyvinyl pyrrolidone high temperature proton exchange membrane according to claim 3, characterized in that: The step S2 comprises: stirring the modified polybenzimidazole in the polyvinyl pyrrolidone solution at 60° C. to 80° C. for 1 h to 3 h to obtain a homogeneous solution of the modified polybenzimidazole and polyvinyl pyrrolidone.

7. The method for preparing a modified polybenzimidazole-polyvinyl pyrrolidone high temperature proton exchange membrane according to claim 3, characterized in that: In the step S3, the heating evaporation temperature is 60° C. to 80° C. and maintained for 15 h to 25 h.

8. The method for preparing a modified polybenzimidazole-polyvinyl pyrrolidone high temperature proton exchange membrane according to claim 3, characterized in that: In the step S4, the concentration of the phosphoric acid is 70 wt% to 98 wt%, and the soaking temperature is 90° C. to 110° C.

9. A membrane electrode, characterized in that: The invention comprises the modified polybenzimidazole-blended polyvinyl pyrrolidone high temperature proton exchange membrane as claimed in claim 1 or 2.

10. A fuel cell, characterized in that: A membrane electrode comprising the membrane electrode according to claim 9.

Citation Information

Patent Citations

  • Non-ionized PBI / PVP membrane, preparation method thereof and flow battery

    CN112225931A

  • Proton conducting polymers prepared by direct acid casting

    US5716727A

Cited By

  • Membrane electrode, preparation method thereof and high-temperature proton exchange membrane fuel cell

    CN120657182A

  • High-temperature proton exchange membrane, preparation method thereof and high-temperature proton exchange membrane fuel cell

    CN120809886A